TINJAUAN HUKUM ISLAM TERHADAP PERTIMBANGAN HAKIM TENTANG HAK EKSEKUTOR FIDUSIA ATAS SERTIFIKAT JAMINAN FIDUSIA (Analisis Putusan Mahkamah Konstitusi Nomor 18/PUU-XVII/2019) - Muhammad Zuhal Haris (AL-BAYAN: JURNAL HUKUM DAN EKONOMI ISLAM, 2022)
Law Number 42 of 1999 concerning fiduciary guarantees, especially Article 15 paragraph (2) and paragraph (3), was sued to the Constitutional Court in addition to being contrary to the 1945 Constitution, also due to objections from the plaintiffs, in this case the debtor who felt aggrieved. with the fiduciary executor rights carried out by creditors in executing fiduciary guarantees. With the lawsuit to the Constitutional Court regarding Article 15 paragraph (2) and paragraph (3) The purpose of this study is to analyze the judges' considerations in the decision of the Constitutional Court No. 18/PUU-XVII/2019, to analyze how Islamic law reviews the decision of the Constitutional Court Number 18/ PUU-XVII/2019. This type of research uses qualitative research methods with a library research approach that is descriptive analytic, and uses the theory of al-masyaqqah tajlibu al-taisīr. The results of this study are: Judges of the Constitutional Court are of the opinion that the petition of the Petitioners can be justified and reasoned according to law in part related to the unconstitutionality of the norms of Article 15 paragraph (2) and paragraph (3) of Law 42/1999, Constitutional Court Decision Number 18/PUU-XVII /2019 has fulfilled the sense of justice and the element of convenience for the parties by providing clear legal definitions and meanings in accordance with shari'a principles and fiqh principles as a solution in knowing general principles and knowing legal advice on contemporary problems